Further delineation of the NTHL1 associated syndrome: A report from the French Oncogenetic Consortium. Issue 5 (12th February 2021) - Boulouard, Flavie; Kasper, Edwige; Buisine, Marie‐Pierre; Lienard, Gwendoline; Vasseur, Stéphanie; Manase, Sandrine; Bahuau, Michel; Barouk Simonet, Emmanuelle; Bubien, Virginie; Coulet, Florence; Cusin, Véronica; Dhooge, Marion; et al.
Abstract: Biallelic pathogenic variants in the NTHL1 (Nth like DNA glycosylase 1) gene cause a recently identified autosomal recessive hereditary cancer syndrome predisposing to adenomatous polyposis and colorectal cancer. Half of biallelic carriers also display multiple colonic or extra‐colonic primary tumors, mainly breast, endometrium, urothelium, and brain tumors. Published data designate NTHL1 as an important contributor to hereditary cancers but also underline the scarcity of available informations. Thanks to the French oncogenetic consortium (Groupe Génétique et Cancer), we collected NTHL1 variants from 7765 patients attending for hereditary colorectal cancer or polyposis (n = 3936) or other hereditary cancers (n = 3829). Here, we describe 10 patients with pathogenic biallelic NTHL1 germline variants, that is, the second largest NTHL1 series. All carriers were from the "colorectal cancer or polyposis" series. All nine biallelic carriers who underwent colonoscopy presented adenomatous polyps. For digestive cancers, average age at diagnosis was 56.2 and we reported colorectal, duodenal, caecal, and pancreatic cancers. Extra‐digestive malignancies included sarcoma, basal cell carcinoma, breast cancer, urothelial carcinoma, and melanoma. Although tumor risks remain to be precisely defined, these novel data support NTHL1 inclusion in diagnostic panel testing. Colonic surveillance should be conducted based on MUTYH recommendations while extra‐colonic surveillance has to be defined. Abstract : Thanks to the French oncogenetic consortium, NTHL1 analysis for 7765 patients allowed the identification of 10 new patients carrying biallelic pathogenic NTHL1 variations. All biallelic carriers who underwent colonoscopy presented adenomatous polyps and four patients had multiple primary tumors. The file of colorectal cancer or adenomas is licensed under the Creative Commons Attribution 3. Unported license (Author : Blausen Medical Communications, Inc.)